Development and Evaluation of Local Snack-Based Complementary Foods for Toddlers Aged 12–23 Months: Nutritional Adequacy, Acceptability, and Cost Feasibility - Sunarto Sunarto; Estuasih Dyah Pertiwi; Dyah Nur Subandriani; Addina Rizky Fitriyanti; Zuhria Ismawanti; Arwin Muhlihsoh; Mohamad Reza Assidhiq (Journal of Health and Nutrition Research, 2026)
Screening data from 412 toddlers in the Tlogosari Wetan Community Health Center area in 2024 revealed a 9.7% prevalence of wasting, with 45% of cases occurring in children aged 12–23 months. Furthermore, 47.5% of toddlers in local supplementary feeding programs did not consume their full portions, primarily due to limited flavor variety and poor taste acceptability. This study aimed to develop and evaluate the nutritional adequacy, sensory acceptability, and cost feasibility of local snack-based complementary foods (CF) for toddlers aged 12–23 months. A five-stage Research and Development (R&D) design was employed, encompassing preliminary research, planning, product development, expert testing, and field testing. Sensory evaluation was conducted by six expert panelists using hedonic and hedonic quality tests. Field trials involved 26 toddlers to assess acceptance using the Comstock method for food residue analysis. Data were analyzed using Repeated Measures ANOVA and Fisher’s Exact tests. Six CF menus were successfully developed, all meeting national nutritional standards, with an energy content of 229–275 kcal, protein 9–11.3 g, fat 11.2–17.2 g, and a protein-energy ratio (PER) of 13.8–16.4%. The "Finger Rice Stick & Tempe Pudding" menu achieved the highest hedonic score for texture and overall preference (p = 0.009). Toddler acceptance reached 87.2%, with intake levels ranging from 58.9% to 81.3% for energy and protein. Cost analysis indicated the products were affordable, with production costs ranging from IDR 4,330 to IDR 8,417 per menu. The developed local snack-based complementary foods are nutritionally adequate, organoleptically acceptable, and economically feasible. These findings suggest their potential for integration into community-level nutrition programs to support stunting and wasting prevention efforts